2023
DOI: 10.1063/5.0166469
|View full text |Cite
|
Sign up to set email alerts
|

Computational optimal transport for molecular spectra: The fully continuous case

Nathan A. Seifert,
Kirill Prozument,
Michael J. Davis

Abstract: Computational optimal transport is used to analyze the difference between pairs of continuous molecular spectra. It is demonstrated that transport distances which are derived from this approach may be a more appropriate measure of the difference between two continuous spectra than more familiar measures of distance under many common circumstances. Associated with the transport distances is the transport map which provides a detailed analysis of the difference between two molecular spectra and is a key componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…While CDF appears to alleviate the need for precise energy alignment, the success of model trained on simulated spectra toward inference from experimental measurements still depends heavily on the accuracy of the simulated spectral shape. Although this study focused on a specific technique (XANES) and a specific edge for a family of battery materials, the use of CDF may be generally advantageous for spectroscopic studies, as shown in recent work on quantitative metrics for comparing molecular spectra. …”
Section: Discussionmentioning
confidence: 99%
“…While CDF appears to alleviate the need for precise energy alignment, the success of model trained on simulated spectra toward inference from experimental measurements still depends heavily on the accuracy of the simulated spectral shape. Although this study focused on a specific technique (XANES) and a specific edge for a family of battery materials, the use of CDF may be generally advantageous for spectroscopic studies, as shown in recent work on quantitative metrics for comparing molecular spectra. …”
Section: Discussionmentioning
confidence: 99%